Anatomical Factors that Can Predict the Structure of Lamina Papyracea for Endoscopic Sinus Surgery. (9th April 2020) - Ohira, Shinya; Matsuura, Kentaro; Matsui, Hidehito; Nakamura, Mitsuto; Kamiyama, Kazuhisa; Kajiwara, Riko; Inoue, Akiko; Wada, Kota
Abstract : Objectives: This study investigated morphological variations of lamina papyracea, the structure that should be carefully considered when opening posterior ethmoid sinus during endoscopic sinus surgery, to avoid injury. Study design: This study employed axial, coronal, and sagittal computed tomography. Methods: Using computed tomography images of 228 face‐sides, various anatomical parameters were determined: distances of the anterior and posterior ethmoid arteries from the skull base, and from the third lamella; changes in the angles of the lamina papyracea at the anterior and posterior ethmoid sinuses; and presence or absence of supraorbital ethmoid cell (SECs), Onodi cell, and Haller cell. The relationship between the distances which indicate the point of maximum projection by the lamina papyracea among third lamina and posterior ethmoid artery into the posterior ethmoid sinus and these anatomical factors were analyzed statistically. Results: The projection distance of lamina papyracea into the posterior ethmoid sinus was −2.6 mm to 3.4 mm, and in 41.2% of cases, projection in the direction of the nasal cavity was greater than that of the lamina papyracea at the anterior ethmoid sinus. This distance increased with increasing distance of the maximum projection point from the skull base and increasing floating distances of the anterior and posterior ethmoid arteries. The number of subjects with large projection distances was increased among those with floating posterior ethmoid arteries. In addition, subjects with SECs had significantly greater projection distances. Conclusions: Particular care should be taken to avoid injury to the lamina papyracea when opening the posterior ethmoid sinus in subjects with floating anterior or posterior ethmoid arteries, and/or SEC. Level of Evidence: 4 Laryngoscope, 131:E19–E25, 2021